Pupils with social, emotional and mental health special needs: Perceptions of how restrictive physical interventions impact their relationships with teaching staff. (January 2021) - Willis, J.; Harrison, A.; Allen, J.L.
Abstract: Positive teacher-child relationships (TCRs) are vital for pupil well-being and are especially important for at-risk children. This qualitative study investigated the impact of restrictive physical interventions (RPIs) on TCRs in focus groups comprising ten boys aged 9–11 years attending two special schools in England. We examined the immediate and post incident impact of RPIs on the TCRs of two groups: students who have experienced RPIs and those who have witnessed RPIs. A range of consequences for student well-being, educational support and the TCR were identified. The implications of current study findings for the prevention and implementation of RPIs are discussed. Highlights: The present study examined the impact of restrictive physical intervention (RPI) on the teacher-child relationship (TCR). This qualitative study included ten boys aged 9 to 11 years in two special education schools in England. Student perspectives were obtained during focus groups using photographic stimuli and hypothetical scenarios. Pupils reported negative and positive consequences of RPIs for student well-being, educational support and the TCR. Pupils who witnessed RPIs perceived a longer timeframe for re-establishing a positive TCR compared to those who had directly experienced RPIs.